2000
DOI: 10.1007/pl00007683
|View full text |Cite
|
Sign up to set email alerts
|

Detection of radiation effects using recombinant bioluminescent Escherichia coli strains

Abstract: Effects of ionizing radiation (0.1-500 Gy) on recombinant Escherichia coli cells containing the stress promoters recA, grpE, or katG, fused to luxCDABE, were characterized by monitoring transcriptional responses reflected by the bioluminescent output. The minimum dose of gamma-irradiation detected by E. coli DPD2794 (recA::luxCDABE) was about 1.5 Gy, while the maximum response was obtained at 200 Gy. The amount of emitted bioluminescence increased proportionally with the gamma-ray doses which were found to eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…This new strain (TVA8) was used as a whole-cell reporter for benzene, toluene, ethylbenzene, and xylene (BTEX) sensing and bioavailability determination (2). Novel applications for bacterial luxAB as reporter genes are still being developed, including the use of recombinant E. coli cells containing the stress promoter recA fused to luxCDABE as a biosensor for ionizing radiation (40). In addition, it is possible to use a biosensor to assess changes in effluent toxicity (8,45) rather than monitoring exact toxin concentrations through measurement of bioluminescence quenching.…”
Section: Applications Of Bioluminescence For Environmental Microbiologymentioning
confidence: 99%
“…This new strain (TVA8) was used as a whole-cell reporter for benzene, toluene, ethylbenzene, and xylene (BTEX) sensing and bioavailability determination (2). Novel applications for bacterial luxAB as reporter genes are still being developed, including the use of recombinant E. coli cells containing the stress promoter recA fused to luxCDABE as a biosensor for ionizing radiation (40). In addition, it is possible to use a biosensor to assess changes in effluent toxicity (8,45) rather than monitoring exact toxin concentrations through measurement of bioluminescence quenching.…”
Section: Applications Of Bioluminescence For Environmental Microbiologymentioning
confidence: 99%
“…Gamma irradiation causes damage to the DNA of cells (Villavicencio et al, 2004;Lee and Levin, 2008). The types of DNA damage experienced may be: i) direct physical effects of ionizing radiation with primary free radicals, and indirect biochemical effects from reactive oxygen species resulting in double-strand breaks; ii) single-strand breaks; and iii) base pair substituting mutations due to the conversion of pyrimidine bases to 5-(hydroxymethyl) uracil, 5-formyluracil, 5-hydroxycytosine, and 5-hydroxyuracil (Jung, 1997;Lydersen and Pettijohn, 1997;Min et al, 2000) In Gram-negative bacteria, the outer membrane plays an important role in infection and pathogenicity toward the host (Tsolis, 2002). In the outer membrane, proteins play a crucial role during many cellular and physiological processes (Qian et al, 2008).…”
Section: Identification Of Outer Membrane Proteins Of Vibrio Parahaemmentioning
confidence: 99%
“…For better expression there are reports on many bioluminescent reporter bacteria that have been engineered by fusing a lux gene construct under the control of an inducible promoter [14]. Bioluminescences from such fused lux constructs have been used to quantify augmented bacteria in the contaminated environments [14,32]. However, Nunes‐Halldorson and Norma‐Letícia [14], in their review on bioluminescent bacteria suggested that fuse lux gene constructs does not work well for gram‐negative bacteria.…”
Section: Discussionmentioning
confidence: 99%